Saqoot-e-Qalat : Wajohat, Waqiat va Asrat - Pervez Ahmad (Lahore Fiction House, 2017)
Historical study of Kalat District, Pakistan formerly Kalat (Princely State) with special reference to its relations with British in India.
Include Index
Keywords: Asia--Kalat (Princely State) -- Pakistan--Kalat District -- Pakistan--Balochistan